2011
DOI: 10.1111/j.1399-5618.2011.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of bipolar depressed patients receiving lamotrigine as add-on to lithium with the possibility of the addition of paroxetine in nonresponders: a randomized, placebo-controlled trial with a novel design

Abstract: In patients with bipolar depression, despite continued use of lithium, addition of lamotrigine revealed a continued benefit compared to placebo throughout the entire study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 32 publications
1
53
0
1
Order By: Relevance
“…Another study reported that valproate was more efficacious than lithium when added to antidepressants for the prevention of bipolar depression [242], and a recent double-blind study suggested that adding an antidepressant (bupropion, sertraline or venlafaxine) on a mood stabilizer improved both the acute-phase outcome and after 1-year follow-up without inducing mania [17]. One study reports that adding lamotrigine to lithium was better than placebo in patients with bipolar depression [517] and its extension with the addition of paroxetine gave some additional positive results [516]. There is also one positive add-on study on long-acting injectable risperidone [320].…”
Section: Combination and Add-on Treatmentmentioning
confidence: 97%
See 1 more Smart Citation
“…Another study reported that valproate was more efficacious than lithium when added to antidepressants for the prevention of bipolar depression [242], and a recent double-blind study suggested that adding an antidepressant (bupropion, sertraline or venlafaxine) on a mood stabilizer improved both the acute-phase outcome and after 1-year follow-up without inducing mania [17]. One study reports that adding lamotrigine to lithium was better than placebo in patients with bipolar depression [517] and its extension with the addition of paroxetine gave some additional positive results [516]. There is also one positive add-on study on long-acting injectable risperidone [320].…”
Section: Combination and Add-on Treatmentmentioning
confidence: 97%
“…A more recent trial reported that the combination of risperidone plus paroxetine was not more efficacious than either agent alone [447], and this should be interpreted by having in mind the negative trial of paroxetine vs. quetiapine [339]. A more recent study reported that adding lamotrigine to lithium was better than placebo in patients with bipolar depression at week 8 [517]; however, it is questionable whether the effect persists beyond week 12 [515,516]. Another recent 8-week trial on 52 incomplete responders utilized adding carbamazepine or oxcarbazepine (600-1,200 mg daily) during maintenance treatment to lithium.…”
Section: Combination and Add-on Treatmentmentioning
confidence: 97%
“…During a one-year extension phase of an RCT, median time to relapse or recurrence was longer among responders receiving lamotrigine compared to those receiving placebo as an addon to lithium ± paroxetine (ten versus 3.5months) (164).…”
Section: Pharmacological Treatments For Maintenance Therapymentioning
confidence: 99%
“…Pharmacological therapy is often the first-line treatment for BD, followed by psychological (Oud et al, 2016) and psychosocial interventions (Goodwin et al, 2008). In addition to lithium and anticonvulsants (van der Loos et al, 2011;Yildiz et al, 2015), antipsychotic agents have also shown promising efficacy for bipolar mania (Yildiz et al, 2011) and depression (Goodwin et al, 2016).…”
Section: Introductionmentioning
confidence: 99%